Lincoln and the Court - McGinty, Brian (Harvard University Press, 2008)
In a meticulously researched and engagingly written narrative, Brian McGinty rescues the story of Abraham Lincoln and the Supreme Court from long and undeserved neglect, recounting the compelling history of the Civil War president's relations with the nation's highest tribunal and the role it played in resolving the agonizing issues raised by the conflict. Lincoln was, more than any other president in the nation's history, a "lawyerly" president, the veteran of thousands of courtroom battles, where victories were won, not by raw strength or superior numbers, but by appeals to reason, citations of precedent, and invocations of justice. He brought his nearly twenty-five years of experience as a practicing lawyer to bear on his presidential duties to nominate Supreme Court justices, preside over a major reorganization of the federal court system, and respond to Supreme Court decisions--some of which gravely threatened the Union cause. The Civil War was, on one level, a struggle between competing visions of constitutional law, represented on the one side by Lincoln's insistence that the United States was a permanent Union of one people united by a "supreme law," and on the other by Jefferson Davis's argument that the United States was a compact of sovereign states whose legal ties could be dissolved at any time and for any reason, subject only to the judgment of the dissolving states that the cause for dissolution was sufficient. Alternately opposed and supported by the justices of the Supreme Court, Lincoln steered the war-torn nation on a sometimes uncertain, but ultimately triumphant, path to victory, saving the Union, freeing the slaves, and preserving the Constitution for future generations